2020
DOI: 10.1186/s12894-020-00595-5
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative intraocular pressure changes during robot-assisted radical prostatectomy: associations with perioperative and clinicopathological factors

Abstract: Background: Steep Trendelenburg position (ST) during robot-assisted radical prostatectomy (RARP) poses a risk of increase in intraocular pressure (IOP) in men receiving robot-assisted radical prostatectomy (RARP). The aim of the study was to identify clinicopathological factors associated with increased IOP during RARP. Methods: We prospectively studied 59 consecutive prostate cancer patients without glaucoma. IOP was measured at 6 predefined time points before, during and after the operation (T1 to T6). Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These effects result in a decrease in cerebral and ocular perfusion pressure, increasing the risk of postoperative cognitive dysfunction and ocular complications. It has been reported that the IOP value decreased after the induction of anesthesia and increased after the induction of pneumoperitoneum in steep Trendelenburg position ranging between 5 and 8 mmHg [39,40]. The longer was the console time, higher the increase in IOP [38 && ].…”
Section: Intraocular Pressurementioning
confidence: 99%
“…These effects result in a decrease in cerebral and ocular perfusion pressure, increasing the risk of postoperative cognitive dysfunction and ocular complications. It has been reported that the IOP value decreased after the induction of anesthesia and increased after the induction of pneumoperitoneum in steep Trendelenburg position ranging between 5 and 8 mmHg [39,40]. The longer was the console time, higher the increase in IOP [38 && ].…”
Section: Intraocular Pressurementioning
confidence: 99%
“…Most studies are small and limited, measuring intraocular pressure mostly in nonglaucomatous subjects. [173][174][175][176][177][178][179][180] Head-down Positioning in Subjects with Glaucoma: Nonsurgical. Moderate head-down tilting can be used as a provocative test to identify patients who progress to development of glaucoma.…”
Section: Preoperative Evaluation and Anesthetic Carementioning
confidence: 99%
“…Most studies are small and limited, measuring intraocular pressure mostly in nonglaucomatous subjects. 173–180…”
Section: Optic Nervementioning
confidence: 99%
“…In 2017 Ozcan et al [ 30 ] analysed the effect of STP on IOP during robotic surgery including 43 RALP cases, finding that the highest IOP was at the end of ST under pneumoperitoneum, whereas in 2020 Shirono et al [ 31 ] discovered that IOP increased 1 h after induction of pneumoperitoneum in STP, remaining elevated in a time-dependent manner during STP.…”
Section: Timingmentioning
confidence: 99%